Expression of γ-H2AX, 53BP1 and Micronuclei as Genome Damage Biomarker of Population in Keang and Salumati Village, Mamuju West Sulawesi Province - A.D. Pratiwi; I.K.H. Basri; S. Purnami; M. Syaifudin; D. Tetriana; D. Yusuf; T. Rahardjo; S. Nurhayati; N. Rahajeng; Y.U. Anggraito; I. Kashiwakura (PPIKSN-BATAN, 2019)
The residents living in high background radiation area have risk to be exposed by ionizing radiation that also potentially cause their DNA damage. The aim of this study was to determine the expression of γ-H2AX, 53BP1 foci and micronuclei in the residentswho live in high background radiation area of Salumati village, Mamuju, West Sulawesi, Indonesia. Twenty one blood samples which consist of 11 from the study area and 10 from control were assessed for their expression of γ-H2AX and 53BPI foci by using specific antibodies and observed under fluorescence microscope whereas micronuclei was detected after being cultured and giemsa stainedaccording to standard procedures. Results showed that both γ-H2AX and 53BP1foci from high background area was lower than that of control area (0.37±0.24vs 0.19±0.11 (p=0.03) for γ-H2AX and 0.61±0.30vs 0.31±0.12 for 53BP1 (p=0.01)). The mean of micronuclei frequency in exposed area was 0.02 (0,01-0,03) while in control area was 0.02 (0.003-0.02). There was statistical significant in corellation between both γ-H2AX, 53BP1 foci with micronuclei index in exposed area (p=0.02, p=0,04 respectively).In conclusion,there was a positive correlation between γ-H2AX and 53BP1 foci to micronuclei and this might be a clue of the occurrence of genome repairing mechanism caused by natural radiation at low dose chronical exposure in thestudied area.